Planning Units of a Comprehensive District Plan: Studies on making a comprehensive district plan in rural areas by inhabitants (III) - USHINO, Tadashi (Transactions of The Japanese Society of Irrigation, Drainage and Reclamation Engineering, 1995)
To implement farm land consolidation that takes into consideration mobilization of land for agricultural use and formation of land use order (planning subjects), the planning units of a comprehensive district plan by inhabitants is going to be made clear. Three types of planning units are considered ; an agricultural settlement unit, a Meiji administrative village unit and a type which combines the former two units. The ideas of municipal authorities and typical examples for each planning unit are gathered, and are examined and their effectiveness is compared, and the points mentioned below are made clear. (1) It's easy to make a comprehensive district plan on an agricultural settlement scale and set the project on foot, if each agricultural settlement leader and municipality are very enthusiastic about it. But it's not enough for accomplishing the above planning subjects. It's impossible to implement the plans at a lot of ordinary agricultural settlements which have lost the substance of traditional village functions. (2) It's suited to perform the above planning subjects on the Meiji administrative village scale. But improvements from the viewpoint of an agricultural settlement are often forgotten. There are less special Meiji administrative villages which have very enthusiastic district leaders, settlement leaders and administrators than special agricultural settlements. (3) A combined type on the Meiji administrative village scale and agricultural settlement scale is effective as a planning unit because it is able to perform the above planning subjects even at a lot of ordinary old villages by using the “Kande method” as a planning method.